Curriculum Models in 21st Century Learning: Challenges for the Future of Education in Indonesia - Munawir Hasan; Wahab, Wahab; Rizki Fathu Rokhman (al-Afkar, Journal For Islamic Studies, 2025)
This article aims to examine the curriculum and orientation of learning in the 21st Century in facing the challenges of the Education era in Indonesia. Given that the curriculum is a very important part of Education and with its dynamic nature, the curriculum must be able to adapt to adjust to changes and developments in the era. The research method that will be used is a qualitative approach involving a literature study as an effort to explore the theories of experts by referring to relevant arguments regarding the problem. The expected results of this study are one of the efforts to prepare students to face this global era, so there needs to be an effort to develop a school curriculum, namely by implementing a curriculum model that is characterized by a global perspective that contains global insights, not just national or local. The world of education is challenged in facing the changing times that continue to change until the current era of globalization. Education must be able to adapt and respond to the needs and demands of the times, especially in the current era of society 5.0 which demands technology-based jobs.